WRKY transcription factors participate in abiotic stress responses mediated by sugar metabolism - Zhang, XueYi; Liu, WanXia; Yin, YiAn; Zheng, Jia; Li, JianAn; Tan, XiaoFeng; Wu, LingLi (Frontiers in Plant Science, 2025)
Plant abiotic stress refers to the unfavorable effects on plants caused by any abiotic factors in a specific environment, such as drought, high temperature, low temperature, etc., which cause disruption of plant physiology and metabolism, and seriously affect the growth and yield of plants. Mounting evidence demonstrates that WRKY transcription factors modulate plant abiotic stress responses by regulating sugar metabolic pathways. Sugar metabolism pathway plays an essential role in plant stress resistance, and WRKY transcription factors, as an important class of regulatory factors, have attracted wide attention for their mechanism of action in abiotic stress. Therefore, this review primarily aims to analyze the structure and classification of WRKY transcription factors, summarize the research progress on how WRKY transcription factors themselves respond to stress, and how they participate in regulating plant stress responses through sugar metabolism pathways. Through in-depth investigation of the relationship between WRKY transcription factors and sugar metabolic pathways we uncovered novel abiotic stress-related gene regulatory networks providing theoretical basis and practical guidance for genetic improvement of plants under abiotic stress.